Green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst - Choudhary, Vasant R.; Dhar, A.; Jana, Prabhas; Jha, Rani; Uphade, B. S. (Green Chemistry, 2005)
Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U3O8, MgO, Al2O3 or ZrO2 in the absence of any solvent.

Generation of hydrogen peroxide via the selective reduction of oxygen by hydrazine sulfate over Br-promoted Pd/Al2O3 catalyst in an aqueous medium at ambient conditions - Choudhary, Vasant R.; Jana, Prabhas; Samanta, Chanchal (Applied Catalysis A-General, 2007)
The in situ generation of H2O2 via the selective reduction of OZ by hydrazine sulfate (in an aqueous medium) has been thoroughly investigated over the Br-promoted Pd(or PdO)/Al2O3 catalyst. The influence of the following factors have been addressed in this study: (a) Br concentration (in the reaction medium or incorporated in the catalyst); (b) reaction conditions (viz. reaction time, temperature); (c) concentrations of reducing agent and phosphoric acid in the reaction medium. Decomposition of N2H4 (from NH4-H2SO4) and its reaction with H2O2 under similar reaction conditions (in the absence of O-2) have also been studied. H2O2, which is an intermediate product of the O-2 reduction, is involved in further consecutive reactions. It can be converted to water via its decomposition and/or reaction with the unconverted NZH(4). In the presence of Br promoter, the later (reaction with unconverted N2H4) is more dominant. Both the consecutive reactions are drastically retarded in the presence of protons and Br promoter. A plausible reaction mechanism has been proposed for illustrating the role of the protons and Br promoter in the selective formation of H2O2 in the O-2 reduction process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: brominated Pd/Al2O3 catalyst; hydrazine sulfate; Hydrogen peroxide; in situ H2O2 generation; oxygen reduction; Pd/Al2O3 catalyst